Kinerja Keuangan Dan Non Keuangan Perhotelan - Hernawati; Yochevyn Agvyanda Sanjaya; Basuki Nugraha (Program Studi Akuntansi - STIE Kesuma Negara Blitar, 2022)
This study aims to analyze the management control system factors on financial and non-financial performance at hotels. The sampling method was purposive sampling. The data analysis used to test the proposed hypothesis is regression analysis and t test Based on the results of data analysis and discussion, it can be concluded that the first hypothesis is proven, this means that the application of a management control system will cause an increase in hotel revenues. The second hypothesis is proven, this means that the implementation of a management control system will lead to increased customer satisfaction and service quality at hotels. For further researchers, they can add other independent variables, such as a reward system to improve the regression model and can be generalized to the research objects of service companies, for example hospitals, PDAMs, Telkom, and so on.